2009
DOI: 10.1007/s10646-009-0328-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker responses in flounder Platichthys flesus from the Polish coastal area of the Baltic Sea and applications in biomonitoring

Abstract: The objective of this study was to investigate the pattern of enzymatic activities, environmental genotoxicity and cytotoxicity in flounder, Platichthys flesus, from the Polish coastal area of the Baltic Sea. Fish were sampled in different contaminated sites in the Gulf of Gdansk and in a reference area outside the gulf. The activities of acetylcholinesterase (AChE), glutathione S: -transferase (GST), catalase (CAT), alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatine kinase (CK), lactat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 65 publications
3
12
0
Order By: Relevance
“…An examination of changes at a tissue level, i.e., histopathology/gametogenesis, could have allowed for a more holistic assessment of the mussels health, yet it was not feasible. AChE activity in flounder was not investigated in the present study, yet the inhibition of its activity in mussels in GoG is in line with earlier studies on flounder and eelpout (Zoarces viviparous) (Napierska and Podolska 2006;Napierska et al 2009). …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…An examination of changes at a tissue level, i.e., histopathology/gametogenesis, could have allowed for a more holistic assessment of the mussels health, yet it was not feasible. AChE activity in flounder was not investigated in the present study, yet the inhibition of its activity in mussels in GoG is in line with earlier studies on flounder and eelpout (Zoarces viviparous) (Napierska and Podolska 2006;Napierska et al 2009). …”
Section: Discussionsupporting
confidence: 88%
“…Chemical contaminants and biomarker responses in various biota in the southern Baltic Sea have been researched in the past (Napierska and Podolska 2006;Napierska et al 2009), yet this study is the first to investigate the pollution and biological effects using three environmental matrices to provide an integrated assessment of environmental quality in this area. The present study aimed at the assessment of (i) priority hazardous substances in flounder (Platichthys flesus), mussels (Mytilus trossulus), and sediment in the context of available environmental target levels, (ii) contaminant-related biological effects through measurements of biomarkers in flounder and mussels in parallel with chemical contaminants, and (iii) sediment toxicity based on sediment bioassays.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported variable HSI results, i.e. increase (Corsi et al, 2003;de la Torre et al, 2007), no change (Barhoumi et al, 2014), and decrease (Napierska et al, 2009) in fish from contaminated sites. Increased HSI values in mosquitofish in the present study may be the result of either hypertrophy (increase in cell size) or hyperplasia (increase in cell number) (van der Oost et al, 2003).…”
Section: Discussionmentioning
confidence: 91%
“…In addition to pollution, several other factors may bias biological responses that are used as biomarkers. Among these, health condition, sex, age, nutritional status/food availability, reproductive phase, metabolic activity, population density, migratory behavior, and environmental factors (e.g., season, and temperature) can alter the physiology of test organisms, thus compromising the effectiveness of biomarker use in environmental analysis, namely for the detection of contamination (van der Oost et al, 2003;Napierska et al, 2009). Additionally, all the mentioned factors can even alter the bioaccumulation profiles and the levels of pollutants in tissues of exposed organisms (Stanic et al, 2006;Vidal-Liñán et al, 2010).…”
Section: Wwwfrontiersinorgmentioning
confidence: 99%